(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Simultaneous interpreting is a highly demanding form of linguistic mediation that requires interpreters to process and reproduce speech in real time. Due to structural differences between languages, time constraints, and cognitive limitations, interpreters frequently apply various strategies to ensure communicative accuracy and clarity. One of the most important strategies is decompression. Decompression refers to the expansion of the source message in the target language in order to clarify meaning, adapt grammatical structures, and ensure comprehensibility for the audience. Unlike compression, which reduces linguistic elements, decompression adds necessary information to maintain equivalence at the level of meaning.